2018
DOI: 10.1002/ange.201801573
|View full text |Cite
|
Sign up to set email alerts
|

Mangan‐katalysierte dehydrierende Alkylierung oder α‐Olefinierung von Alkyl‐N‐heteroarenen durch Alkohole

Abstract: Die Katalyse mit auf der Erde häufig vorkommenden Übergangsmetallen ist eine Option, um unsere seltenen Edelmetallressourcen zu schonen, und ist besonders interessant, wenn neue Reaktivitäts-oder Selektivitätsmuster beobachtet werden. Wirberichten hier über eine neue Reaktion:die dehydrierende Alkylierung oder a-Olefinierung von Alkyl-Nheteroarenen mit Alkoholen. In unserem Labor entwickelte Mangankomplexekatalysieren die Reaktion effizient. Fe-und Co-Komplexe,die durch solcheLiganden stabilisiert sind, sind i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Among several other catalytic complexes screened, Kempe and co‐workers found that Mn ‐ 20 , having a triazine pincer ligand backbone swiftly catalyzed the α‐olefinations of 2‐methylquinolines and N‐heteroarenes. Notably, the corresponding iron and cobalt complexes tested in this study were found to be inactive under a similar condition [93] …”
Section: Synthesis Of Olefinsmentioning
confidence: 54%
See 2 more Smart Citations
“…Among several other catalytic complexes screened, Kempe and co‐workers found that Mn ‐ 20 , having a triazine pincer ligand backbone swiftly catalyzed the α‐olefinations of 2‐methylquinolines and N‐heteroarenes. Notably, the corresponding iron and cobalt complexes tested in this study were found to be inactive under a similar condition [93] …”
Section: Synthesis Of Olefinsmentioning
confidence: 54%
“…In 2018, Kempe [93] and co‐workers and Maji [94] and co‐workers independently demonstrated manganese catalyzed olefination reaction of alkyl‐substituted heteroarenes with alcohols (Scheme 44). Among several other catalytic complexes screened, Kempe and co‐workers found that Mn ‐ 20 , having a triazine pincer ligand backbone swiftly catalyzed the α‐olefinations of 2‐methylquinolines and N‐heteroarenes.…”
Section: Synthesis Of Olefinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kempe and co‐workers reported a manganese‐pincer catalysed α‐olefination of nitrogen‐containing heteroarenes using primary alcohols (Scheme ) . Among the various catalytic complexes screened the manganese‐PN 5 P pincer 113 was found to be an active catalyst while the corresponding iron and cobalt complexes were inactive.…”
Section: Synthesis Of Olefinsmentioning
confidence: 99%
“… Plausible catalytic cycle and reaction mechanism for the Mn‐catalysed alkene synthesis of methylheterocycles by Kempe et al. (reproduced with permission from Ref …”
Section: Synthesis Of Olefinsmentioning
confidence: 99%